Outcome after redo coronary artery bypass grafting in patients with ischaemic cardiomyopathy and viable myocardium. Issue 2 (11th August 2006) - Rizzello, V; Poldermans, D; Schinkel, A F L; Biagini, E; Boersma, E; Elhendy, A; Sozzi, F B; Palazzuoli, A; Maat, A; Crea, F; Bax, J J
Abstract : Background: Repeat coronary artery bypass grafting (redo-CABG) in patients with ischaemic cardiomyopathy is associated with high perioperative risk and worse long-term outcome compared with patients undergoing their first CABG. Objective: To assess whether patients with viable myocardium undergoing redo-CABG have a better outcome. Methods: 18 patients with ischaemic cardiomyopathy underwent redo-CABG and 34 underwent their first CABG; all had substantial viability (⩾25% of the left ventricle) on dobutamine stress echocardiography (DSE). Left ventricular ejection fraction (LVEF) and heart failure symptoms were assessed before and 9–12 months after revascularisation. Cardiac event rate was assessed during the follow-up period (median 4 years, 25–75th centile 2.8–4.9 years). Results: The extent of viable myocardium on DSE was comparable in the two groups (11.3 (3.9) segments in patients who underwent redo-CABG v 12.8 (3.0) in patients who underwent their first CABG; p = NS). LVEF improved from 32% (9%) to 39% (12%); p = 0.01, in patients who underwent redo-CABG and from 30% (7%) to 36% (7%); p<0.01, in those who underwent their first CABG; New York Heart Association class improved from 2.5 (1.1) to 1.9 (0.8); p = 0.03, and from 2.7 (1.0) to 1.8 (0.70); p<0.01, respectively. In patients who underwent redo-CABG, the perioperative mortality was 0, post-surgery inotropic support was needed in 11% of the patients and mid-term (4-year) survival was 100%, with a total event rate of 28%. All these variables were not statistically different from patients who underwent their first CABG (p = 0.50, 0.90, 0.08 and 0.81, respectively). Conclusion: Patients with ischaemic cardiomyopathy and substantial viability undergoing redo-CABG benefit from revascularisation in terms of improvement in LVEF, heart failure symptoms, angina and mid-term prognosis.